Cold water immersion (cryotherapy) for preventing muscle soreness after exercise - Diong, J.; Kamper, S. J. (British Journal of Sports Medicine, 2014)
This section features a recent systematic review that is indexed on PEDro, the Physiotherapy Evidence Database (www.pedro.org.au). PEDro is a free, web-based database of evidence relevant to physiotherapy. Intense exercise involving eccentric muscle contractions often leads to delayed onset muscle soreness. Eccentric muscle contractions cause damage to muscle fibres which lead to pain, stiffness and loss in joint range of motion. The anti-inflammatory effects of cold water immersion, a form of cryotherapy where the limb(s) or body is submerged in a cold water bath, are thought to reduce pain and swelling following acute soft tissue injury. Cold water immersion immediately after exercise may have anti-inflammatory effects and prevent delayed onset muscle soreness, however these effects remain unclear.